Prenatal and Postnatal Cigarette Smoke Exposure Is Associated With Increased Risk of Exacerbated Allergic Airway Immune Responses: A Preclinical Mouse Model - Janbazacyabar, Hamed; van Bergenhenegouwen, Jeroen; Garssen, Johan; Leusink-Muis, Thea; Ark, Ingrid van; van Daal, Marthe T.; Folkerts, Gert; Braber, Saskia (Frontiers in Immunology, 2021)
Increased exposure to household air pollution and ambient air pollution has become one of the world’s major environmental health threats. In developing and developed countries, environmental cigarette smoke (CS) exposure is one of the main sources of household air pollution (HAP). Moreover, results from different epidemiological and experimental studies indicate that there is a strong association between HAP, specifically CS exposure, and the development of allergic diseases that often persists into later life. Here, we investigated the impact of prenatal and postnatal CS exposure on offspring susceptibility to the development of allergic airway responses by using a preclinical mouse model. Pregnant BALB/c mice were exposed to either CS or air during pregnancy and lactation and in order to induce allergic asthma the offspring were sensitized and challenged with house dust mite (HDM). Decreased lung function parameters, like dynamic compliance and pleural pressure, were observed in PBS-treated offspring born to CS-exposed mothers compared to offspring from air-exposed mothers. Maternal CS exposure significantly increased the HDM-induced airway eosinophilia and neutrophilia in the offspring. Prenatal and postnatal CS exposure increased the frequency of Th2 cells in the lungs of HDM-treated offspring compared to offspring born to air-exposed mothers. Offspring born to CS-exposed mothers showed increased levels of IL-4, IL-5 and IL-13 in bronchoalveolar lavage fluid compared to offspring from air-exposed mothers. Ex-vivo restimulation of lung cells isolated from HDM-treated offspring born to CS-exposed mothers also resulted in increased IL-4 production. Finally, serum immunoglobulins levels of HDM-specific IgE and HDM-specific IgG1 were significantly increased upon a HDM challenge in offspring born to CS-exposed mothers compared to offspring from air-exposed mothers. In summary, our results reveal a biological plausibility for the epidemiological studies indicating that prenatal and postnatal CS exposure increases the susceptibility of offspring to allergic immune responses.